2019
DOI: 10.1371/journal.pone.0210692
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal malaria chemoprevention packaged with malnutrition prevention in northern Nigeria: A pragmatic trial (SMAMP study) with nested case-control

Abstract: Integrating seasonal malaria chemoprevention (SMC), recommended by the WHO since 2012 to prevent malaria infection, with nutrition interventions may improve health outcomes and operational efficiencies. This study assessed the effects of co-packaging interventions on distribution coverage, nutrition, and clinical malaria outcomes in northern Nigeria. From August to November 2014, community volunteers delivered sulfadoxine-pyrimethamine and amodiaquine (SP-AQ) door-to-door each month to approximately 7,000 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…While this was not in SMC's setting, a study comparing various malaria preventive regimens in Ugandan children showed that adherence to a 3-day course of dihydroartemisinin-piperaquine was much higher when reported by the caregiver (~100%) compared to the unbiased concentration of drugs [7]. A lower adherence was found using a longitudinal study in Nigeria by Ward et al Their research found that the adherence was 83.8% [8]. Several factors may explain these observations, and a mix of these reasons rather than one alone is likely responsible.…”
Section: Discussionmentioning
confidence: 96%
“…While this was not in SMC's setting, a study comparing various malaria preventive regimens in Ugandan children showed that adherence to a 3-day course of dihydroartemisinin-piperaquine was much higher when reported by the caregiver (~100%) compared to the unbiased concentration of drugs [7]. A lower adherence was found using a longitudinal study in Nigeria by Ward et al Their research found that the adherence was 83.8% [8]. Several factors may explain these observations, and a mix of these reasons rather than one alone is likely responsible.…”
Section: Discussionmentioning
confidence: 96%
“…Even though this study does not provide clear evidence about an association between malnutrition and malaria risk, it shows clearly that both conditions are causing a high disease burden. The use of SMC as a platform for nutritional interventions requires further investigation, and could have important impacts on nutritional status and malaria burden [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given current interest in incorporating nutritional screening or other nutritional interventions with SMC delivery [ 17 ], it is important to understand more about the nutritional status of children immediately prior to the rainy season, when SMC delivery begins. Clarifying the direct effect of malnutrition on malaria risk would help in understanding whether nutritional interventions might have the potential to assist with malaria control in the Sahel region.…”
Section: Introductionmentioning
confidence: 99%
“…In Plasmodium falciparum endemic areas, children having stunting and underweight were more infected by Plasmodium, but parasite density remains lower [21,22]. reduce parasite density and improve nutritional status in children [23]. Other parameters as family income, mother's characteristics, other pathologies were not investigated and could be influenced children nutritional status [24][25][26] are the limit of this study.…”
Section: Discussionmentioning
confidence: 99%